Impressões da Nação: o imaginário político luso-brasileiro no periodismo vintista (1820-1823) - Silva, Jhonatas Elyel (2022)
From the Liberal Revolution of 1820 on it will be noticed an explosion of new printed vehicles launched both in Portugal and Brazil, with the purpose of writing the first words of that history and instructing the public about the order of things in gestation. Some of these newspapers were the Astro da Lusitânia, the Conciliador do Maranhão, the Correio do Rio de Janeiro, the Diário do Rio de Janeiro, the Semanário Cívico and O Paraense. Through the study of the linguistic images within these vehicles and with the methodological support of the French Discourse Analysis, it was aimed to understand the contributions of this periodic press to a process which includes more than mediating power relations and transmitting events. For this, the research identified (quantitatively) the most pertinent images of the political imaginary present in the documental corpus, before proceeding to a characterization of the intercontinental dialogue (between the Brazilian provinces from where these discourses were produced) and transatlantic (taking into consideration the possibility of a United Kingdom of Portugal, Brazil and Algarve or Portuguese Nation, as one of the realities of that moment) and the problematization of the dynamics between press and society that made emerge proposals that went from the said United Kingdom and the imminent rupture of the Centre-South, to the attempt to establish a territory in the Northern provinces of Brazil as remnants of the Lusitanian colonial Empire. Thus, we conclude the place of these vehicles not only as legitimating means of social order, but as true powers of construction and deconstruction of meaning, condensing temporalities, dilating spatialities and laying the foundations not only of the Brazilian nation-state as we know it today and the very civilizing logic that sustains it, but questioning and displacing - through the particular cases of each periodical - our universalizing understanding of the event in question - the process of formation of the Brazilian State. In short, catalyzing instruments of these discursive images and political affections in favor of the various projects of nationhood that were conceived in the gap left between the dismantling of the Ancient Regime and the constitution of the modern world.